(untitled) (Historia, 2021)
In this review article certain aspects of the history of the War for Southern Africa of 1966 to 1989, as well as its consequences, are evaluated critically by looking at three recent publications on interrelated topics. The most controversial of the three publications deals with the highly-classified operations conducted from 1978 to 1988 by the South African Special Forces in Angola and Mozambique – with invaluable assistance provided by the South African Navy. The second book focuses on the war in Angola in the years 1975 to 1989, looking at the conflict from the South African, Russian, Cuban and East German point of view, and also includes an invaluable list of sources that deal with the war. The third book explores, inter alia, the impact that the years of conflict had (and still have) on South African society and culture. These three publications form part of the continued outpouring of books on the years of struggle in southern Africa, but are of a much higher standard than some of the many popular works of recent years.